Rapamycin adjuvant and exacerbation of severe influenza in an experimental mouse model - Huang, Ching-Tai (Sci Rep, 2017)
Influenza virus infection often causes severe disease and acute respiratory distress syndrome. It is a common belief that overwhelming immune response contributes to the severe illness. Physicians and researchers have put forth immune modulation as salvage therapy for better recovery. However, empiric corticosteroid failed in both humans and animal models. Reported success with Rapamycin in humans prompted a comprehensive animal study and mechanistic dissection. Here we report the effect of Rapamycin alone or in combination with Oseltamivir for severe influenza in BALB/c mice. We found that Rapamycin had no antiviral effect against H1N1, H3N2 and novel-H1N1 influenza viruses in vitro. Rapamycin alone aggravated the severe disease of PR8 H1N1 influenza virus infection in mice. Timely Oseltamivir anti-viral therapy abolished the disease. Delayed Oseltamivir treatment could not prevent severe illness and Rapamycin adjuvant was associated with exacerbated disease. Rapamycin adjuvant suppressed influenza hemagglutinin antigen-specific T cell immunity and impaired virus clearance from the lungs. It also resulted in intensified lung pathology with increased intra-alveolar edema and hyaline deposition. Rapamycin may work as the salvage therapy for severe influenza but it is very difficult to define the appropriate window for such treatment to take effect.